Pengaruh Pengetahuan Keuangan Dan Sikap Keuangan Terhadap Perilaku Manajemen Keuangan Pada Pelaku Usaha Umkm Fashion Di Kota Malang Pada Saat Pandemi Covid-19 - Anggita Lira Ardhiyanti; N. Rachma; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to test the influence of financial knowledge and financial attitudes on financial management behavior in fashion SMEs in Malang City. This research is a quantitative study with data collection techniques using a questionnaire. The sample in this study amounted to 72 respondents. The sampling tecnique used was puposive sampling method. Primary data processing using mutiple regression analysis. The result of this study indicate that simultaneously the variables of financial knowledge and financial attitudes have a posttive and significant effect on financial management behavior. Partially the variable of financial knowledge has no positive and significant effet on financial management behavior, and financial attitudes have a positive and significant effect on financial management behavior. Keywords : Financial Knowledge, Financial Attitudes, Financial Management behavior